Modelo de referência para o processo de gestão da produção agrícola: ênfase na mecanização - Tatsch, Marcelo Pastoriza (2015)
This research is focused on agricultural mechanization within the context of Brazilian agribusiness and its theme modeling processes, focusing on the description and modeling of the management of the agricultural production process in rural enterprises. From the emphasis of the research that has as main objective to create a reference model for the management process of agricultural production: emphasis on mechanization and in order to achieve the objectives of the study, the author sought information in the literature to promote closer ties between the context and the focus of research, but covers other areas of knowledge considered essential to the development of the thesis, such as: design of systems, processes, planning, agricultural mechanization planning addition of process modeling. The approach of theory and practice occurs through the modeling of the process of administration of agricultural machinery, according to the formalism of modeling, the Núcleo de Ensaio de Máquinas Agrícolas da Universidade Federal de Santa Maria. From the literature review and systematization of this, there was the necessary basis for the creation of the Reference Model for the Management of Agricultural Production Process: Focus on mechanization, which presents in three macrofases: Planning, Sizing, Control and Evaluation. From these eight phases originated: Physical Environment, Production, Operations, Machinery, Workforce, Performance, Capital and Results.